Membrane vesicles released by intestinal epithelial cells infected with rotavirus inhibit T-cell function (2010)
Rotavirus (RV) predominantly replicates in intestinal epithelial cells (IEC), and 'danger signals' released by these cells may modulate viral immunity. We have recently shown that human model IEC (Caco-2 cells) infected with rhesus-RV release a non-inflammatory group of immunomodulators that includes heat shock proteins (HSPs) and TGF-?1. Here we show that both proteins are released in part in association with membrane vesicles (MV) obtained from filtrated Caco-2 supernatants concentrated by ultracentrifugation. These MV express markers of exosomes (CD63 and others), but not of the endoplasmic reticulum (ER) or nuclei. Larger quantities of proteins associated with MV were released by RV-infected cells than by non-infected cells. VP6 co-immunoprecipitated with CD63 present in these MV, and VP6 co-localized with CD63 in RV-infected cells, suggesting that this viral protein is associated with the MV, and that this association occurs intracellularly. CD63 present in MV preparations from stool samples from 36 children with gastroenteritis due or not due to RV were analyzed. VP6 co-immunoprecipitated with CD63 in 3/8 stool samples from RV-infected children, suggesting that these MV are released by RV-infected cells in vivo. Moreover, fractions that contained MV from RV-infected cells induced death and inhibited proliferation of CD4+ T cells to a greater extent than fractions from non-infected cells. These effects were in part due to TGF-?, because they were reversed by treatment of the T cells with the TGF-?-receptor inhibitor ALK5i. MV from RV-infected and non-infected cells were heterogeneous, with morphologies and typical flotation densities described for exosomes (between 1.10 and 1.18g/mL), and denser vesicles ( and gt;1.24g/mL). Both types of MV from RV-infected cells were more efficient at inhibiting T-cell function than were those from non-infected cells. We propose that RV infection of IEC releases MV that modulate viral immunity. © 2010, Mary Ann Liebert, Inc.